INVESTIGATION OF THE TL CHARACTERISTICS OF COMPOSITE PEAK 5 IN THE GLOW CURVE OF LIF:MG, TI (TLD-100) USING NATURALLY AND FURNACE-COOLED SAMPLES FOLLOWING THE 400°C PRE-IRRADIATION ANNEAL. Issue 1 (31st August 2021) - Eliyahu, Ilan; Reshes, Galina; Shapiro, Alex; Biderman, Shlomo; Oster, Leonid; Nemirovsky, Dimitry; Sterenberg, Matan; Ginzburg, Dimitry; Horowitz, Yigal Shalom; Herman, Benny; Assor, Yosef
Abstract: The cooling rate to room temperature following the 400°C pre-irradiation anneal is known to affect the thermoluminescent properties of LiF:Mg, Ti (TLD-100) as a result of migration and clustering of defects during the cooling down process. In this investigation the dose response over an extended dose range from 0.01 to 7000 Gy in both naturally cooled and the much slower furnace-cooled samples has been measured. Glow curve deconvolution based on first-order kinetics is employed to extract the dose response of the various glow peaks. Of especial interest is the behaviour of glow peaks 4, 5a and 5 as a function of dose. The idea is to modify the supralinear dose response of peak 5 from 1 to 30 Gy to a linear behaviour. This dose range is important for clinical therapy and a linear dose response is of substantial advantage leading to both improved accuracy and precision.